2015
DOI: 10.1016/j.eswa.2015.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Declarative process mining in healthcare

Abstract: Clinical guidelines aim at improving the quality of care processes based on evidence-based insights. However, there may be good reasons to deviate from such guidelines or the guidelines may provide insufficient support as they are not tailored towards a particular setting (e.g., hospital policy or patient group characteristics). Therefore, we propose an approach to mediate between event data reflecting the clinical reality and clinical guidelines describing best-practices in medicine. Concretely, we repair and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 54 publications
2
76
0
1
Order By: Relevance
“…Although imperative process modeling languages can also support the flexibility by design principle, declarative process modeling languages are better suited for modeling loosely framed processes as they do not require enumerating the potentially large number of valid process variations (Rovani et al, 2015). Generally, given the large number of allowed process variations in loosely framed processes, less effort will be required to describe the properties that make variations valid or invalid compared to enumerating all the valid process variations explicitly like imperative languages (Goedertier et al, 2015;van der Aalst, 2013).…”
Section: Declare As a Foundationmentioning
confidence: 99%
“…Although imperative process modeling languages can also support the flexibility by design principle, declarative process modeling languages are better suited for modeling loosely framed processes as they do not require enumerating the potentially large number of valid process variations (Rovani et al, 2015). Generally, given the large number of allowed process variations in loosely framed processes, less effort will be required to describe the properties that make variations valid or invalid compared to enumerating all the valid process variations explicitly like imperative languages (Goedertier et al, 2015;van der Aalst, 2013).…”
Section: Declare As a Foundationmentioning
confidence: 99%
“…Seven papers used declarative process mining and its enhancements [26]- [32]. Declarative process mining involves identifying possible execution paths for bridging event data reflecting the clinical reality and clinical guidelines describing best-practice.…”
Section: Resultsmentioning
confidence: 99%
“…Pathways are a distinctive type of clinical guidelines, which specify each step in the care process, rather than stating broad principles that practitioners should follow [17]. Nevertheless, it was observed that there is a gap between these recommendations and actual practices since healthcare processes have large healthcare facilities, multidisciplinary and highly complicated structures, and flexible patient flows [18,19].…”
Section: Evidence-based Medicinementioning
confidence: 99%